Perfil de aplicação acervo Judith Cortesão, como instrumento de curadoria digital: um estudo de equivalências entre a norma ISAD(G) e o conjunto de elementos do Argo - Barcellos, Raquel Siegel (2018)
In 2003, the Federal University of Rio Grande received the donation of the personal collection of the environmentalist, researcher and educator Maria Judith Zuzarte Cortesão. In 2005, the University, together with its Postgraduate Program in Environmental Education (PPGEA), were included in Edict 1/2005 of the Ministry of the Environment for the implementation of a Green Room, and the following year was created the Library Sectoral of the Graduate in Environmental Education Green Room Judith Cortesão with the objective of sheltering the teacher's collection, as well as meeting the specifications of the edict. The donated collection can be classified as a collection of documents and a bibliographic collection in which only what concerns the bibliographic collection received treatment, being he organized, described and available for public consultation in the Argo database. Considering the context presented, the justification for this investigation stems from the need to carry out an interdisciplinary reflection, correlating the contributions of the Archival Science as well as those of the Library Science to the practices of documentary and bibliographic treatment in personal collections, so that appropriate procedures are used for preservation, description, interoperability, diffusion and access of the personal collection of Professor Drª. Maria Judith to Zuzarte Cortesão. In this sense, the theoretical reference emphasizes the central aspects: cultural and documentary heritage; personal archive; documentary and bibliographic treatment; and the use of digital curation as an interdisciplinary practice for description, preservation, interoperability and the sharing of personal collections. It is a research of an applied nature, regarding the approach of the problem, the research is classified as qualitative and from the point of view of its objectives the research is considered exploratory. The data collection took place through direct observation, documentary analysis and also through consultations to the Argo Library Administration System. From the proposition of the work it was possible to diagnose the situation that is the collection accumulated by Judith, as well as identifying and understanding the context and content of the collection in question. Continuing the objectives of the work, a research and analysis of the International Standard of Archival Description (ISAD(G)) / (NOBRADE) and the set of metadata used by the Argo Library Administration System were carried out, which resulted in a mapping of equivalences. As a proposal for a digital curation tool, it was defined and implemented an application profile capable of describing both the bibliographic collection and the documentary collection of the teacher Judith Cortesão getting reliable, refined and interoperable results originating the final product of this dissertation. Concomitant, a survey was carried out on the platform Access to Memory (AtoM) / (ICA-AtoM), listing its main objectives and functionalities, which allowed to use it as a tool to demonstrate and validate the use of the application profile created.